Composition of birds associated with organic cacao farms, Huetar Norte Region, Costa Rica - Carvajal Alfaro, Vanessa (2024)
[Objective] The objective of this investigation was to analyze the composition of birds associated with organic cocoa (Theobroma cacao) crops managed under 3 different types of tree cover. [Methodology] Three census points were established in each farm to record all birds observed and heard in 5-minute sample periods. Counts were conducted in triplicate, both in the early morning and at dusk. Differences in avifauna composition between farms were analyzed using the ANOSIM test. Abundances were transformed using the Decostand function and the Hellinger method in the R-Vegan statistical package. Analysis of clustering of species among plantations was performed using non-metric multidimensional scaling (nMDS) and the Bray-Curtis index. Contribution of species to the dissimilarity between groups was analyzed with the SIMPER module. Statistically significant differences were considered when P ≤ 0.05. [Results] Four hundred and twenty-eight individuals were observed, and classified into 49 species and 23 families. The farms where cocoa plants grow in shadier conditions due to canopy development showed a higher number of species (34) and individuals (146). Bird composition varied significantly between farms (F (1,8) = 3.22; P < 0.02). The mean abundance of 19 species (39.6%) showed significant differences (P < 0.05) when comparing the farms with the most and least shade. [Conclusion] Bird composition is more complex on organic cocoa farms, which have more developed canopies and are near regenerating forests.